SCREENING POST-COLONIALISM AND RED SCARE ABOUT THE 1950S MALAYAN EMERGENCY IN “THE 7TH DAWN” (1964) - Luigi Andrea Berto, (PEOPLE: International Journal of Social Sciences, 2025)
The goal of my paper is to examine the movie “The 7th Dawn (1964)”, directed by British filmmaker Lewis Gilbert (1920-2018) and distributed by United Artists. Based on the novel The Durian Tree (1960) by Australian writer Michael Keon (1918-2006), the film is set during Malaysia's process of independence from Britain in the 1950s. I argue that “The 7th Dawn (1964)” displays sympathies for the peaceful methods of opposing colonialism, stigmatization for the repressive methods of the British but, at the same time, emphasize the existence of the widespread belief in various Western European countries and in USA that independence movements in Southeast Asia were actually a way of creating a communist system in that part of the world